Correlation between handheld digital device use and asthenopia in Chinese college students: a Shanghai study - Xu, Yupeng; Deng, Guoying; Wang, Weiheng; Xiong, Shuyu; Xu, Xun (Acta ophthalmologica (Oxford, England), 2019)
Purpose The purpose of this study was to investigate the use of handheld digital devices and the prevalence of self‐reported asthenopia among college students in China and their potential relationship. Methods Five thousand students were randomly assessed using a self‐reported asthenopia questionnaire. The students’ demographic characteristics and habits regarding digital device use were recorded. Univariate analysis was performed to select potential risk factors, and multivariate logistic regression was used to estimate the odds ratios for the selected risk factors of interest. Results Among the 4786 students who completed the survey, the prevalence of asthenopia was 53.3%. Multivariate analysis revealed significant relationships between asthenopia and each of the following: level of digital reliance (OR 1.350, 95%CI: 1.230–1.481), workload, time spent on computer per day, sex and time spent on handheld digital devices in bed and at desk. Aerobic exercise duration (OR 0.912, 95%CI: 0.839–0.990) was found to be strong predictor of less asthenopia complaints. Conclusion Asthenopia appears to be common among college students in China. Preventative measures against asthenopia include limiting the amount of time spent using digital devices in bed (<0.5 h), adopting a posture of lying on one's back while doing so and engaging in aerobic exercise for more than one hour per day. Furthermore, studies on this topic are needed.